The costs of protecting health in the face of climate change - feasibility lies in proactivity - Asad Saulat Fatimi; Mahmud, Omar (Journal of the Pakistan Medical Association, 2022)
Climate change has and will continue to lead to unexpected weather patterns worldwide. These threaten to increase the risk of numerous diseases and disasters that negatively impact the health of populations. As a developing country, Pakistan must bolster its preparedness for such weather-related health problems by efficienty allocating resources to preventive measures and proactively implementing them. In recent history, torrential rainfall in areas such as Karachi, which usually receive meagre amounts of annual rainfall, has left many economic and health-related issues that harm the health of the population and disrupt healthcare delivery. For example, the massive accumulation of stagnant water following heavy rainfall acts is a breeding ground for mosquitoes. Thus, urban flooding is often accompanied by an increase in mosquito-related diseases such as dengue and malaria (1,2). Furthermore, the presence of airborne and allergenic fungal spores in the environment is positively correlated with increased amounts of rainfall (3). Heavy rain damages infrastructure, such as roads and electricity lines in urban areas. In addition to the disruption of transport and utilities, such damage leads to numerous hospitalizations and deaths in incidents such as motor accidents, burns, electrocution, falling into exposed gutters, drowning, and other similar tragedies (4). Beyond these direct effects on human health, healthcare delivery and resource mobilization are also hindered (5), further hampering the responsiveness and effectiveness of the healthcare system. While measures like disinfection drives may be useful in decreasing rain-related morbidity and mortality, a reactive approach must become an initiative-taking one. With comprehensive analyses of trends, such as those of hospitalizations during the monsoon season or the frequency of rain-related injury and disease in different areas, more informed preventive measures and “evidence-based anticipation” (5) of health burdens can be devised and deployed. Programmes to promote safety measures and awareness can be tailored to the needs of at-risk communities and burdened health-care centres. The allocation of precious resources can be made to those that need them most ahead of destructive weather. Climate change is a stark reality, as is the shortage of resources in developing countries like Pakistan. It is vital to acknowledge the profound impact of destructive weather on the public’s well-being and to act efficiently and proactively to mitigate it.